Robert L. Crouch. Macroeconomics. Nueva York, [N.Y.] : Harcourt Brace Javanovich, 1972. 425 p. - Peña, Raúl de la (Estudios Demográficos y Urbanos, 1974)
ROBERT L. CROUCH, Macroeconomics, Nueva York, Harcourt Brace Javanovich, 1972.